Assessing Energy Efficiency for Economic and Sustainable Development in the Region of European Union Countries - Yan, Dong; Liu, Hongda; Yao, Pinbo (Frontiers in Environmental Science, 2021)
The objective of this research is to estimate the energy saving intensities of nations within the European Union, applying varied equations of the DEA analysis, such as the DEA, modified radial equation, Russel dynamic envelope analysis, the adjusted Russel Dynamic envelope Analysis throughout the period of 2010-2018. Different from other studies, this analysis seeks to unravel the narrative whether the European nations are effective in increasing the EE finance of their respective economies. Regarding this circumstance, different dynamic envelope evaluations were formulated. One primary findings of the lot are nations such as Germany, Sweden or Austria attain robust ecological safeguards performance, seem to be energy less and ecologically efficient, relative to different nations such as the Denmark, Belgium, Spain, France or Ireland. Furthermore, a group of Eastern EU nations attain reduced efficiency marks, that could be categorized as anticipated, as a result of reduced technological implementation within the principal manufacturing sectors. Our prime result depicts that few nations are doing well on the efficiency frontline. Additionally, RE power production expands as nations’ dynamic envelope analysis marks as well as adds to creating inefficient nations nearer to the efficiency frontline. Inversely, the presence of peak time of power consumption reduced the dynamic envelope analysis marks as well as distant from the frontline.